Implementasi Metode Latihan Berjenjang dalam Meningkatkan Prestasi Belajar Peserta didik Kelas V SD Negeri 5 Selebung Ketangga - Lalu A. Hery Qusyairi (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2021)
The objectives of this research are 1). to find out the increase in science learning achievement by using the tiered training method for fifth grade students at SD Negeri 5 Selebung Ketangga, Kec. Keruak East Lombok and 2). To find out the increase in students' learning activities and creativity. This type of research includes classroom action research (CAR). This research was carried out in the form of an action cycle, in the form of science learning on Simple Aircraft material with the tiered training method. Each action cycle consists of four stages, namely action planning, action implementation, observation, and reflection. The results of this action research can be described as follows: The use of tiered training methods can improve science learning outcomes in 5th grade students of SD Negeri 5 Selebung Ketangga. This can be seen from the number of students who succeeded in achieving the minimum required learning completeness criteria which experienced a significant increase in each cycle of action. The number of students who succeeded in achieving the criteria for mastery learning in the first cycle were 14 people (64%) then increased to 16 people (73%) in the second cycle and increased again to 19 people (86%) in the third cycle. Science learning in 5th grade students of SD Negeri 5 Selebung Ketangga is proven to be able to increase students' learning activities and creativity. It can be seen from all students who are actively asking questions, both with friends and with the teacher. Students who were originally passive, with learning using the tiered training method, their learning activities and creativity gradually always increased.